A 2.5-D glass micromodel for investigation of multi-phase flow in porous media. Issue 4 (3rd February 2017) - Xu, Ke; Liang, Tianbo; Zhu, Peixi; Qi, Pengpeng; Lu, Jun; Huh, Chun; Balhoff, Matthew
Abstract : A novel method to fabricate micromodels with varying depth (2.5-D) was developed, which allows more realistic investigation on flow in natural 3-D porous media. Abstract : We developed a novel method for fabrication of glass micromodels with varying depth (2.5-D) with no additional complexity over the 2-D micromodels' fabrication. Compared to a 2-D micromodel, the 2.5-D micromodel can better represent the 3-D features of multi-phase flow in real porous media, as demonstrated in this paper with three different examples. Physically realistic capillary snap-off and the formation of isolated residual oil droplets were realized, which is not possible in 2-D micromodels. Droplet size variation during an emulsion flooding was investigated on the 2.5-D micromodel, showing that the droplet size decreases sharply at the inlet, with little change in size downstream of the micromodel. Displacement of light oil with ultra-low interfacial tension (IFT) surfactant was conducted in the 2.5-D micromodel, where we were able to visualize the generation and flowing of a microemulsion phase, which agrees with, and explains observations in experiments of more complex porous media.